SUPERVISION OF KARAOKE BUSINESS LICENSING IN JEMBER CITY (STUDY IN THE DINAS OF INVESTMENT AND ONE-DOOR INTEGRATED SERVICE, JEMBER DISTRICT) - Kahar Haerah Haerah; Humaidin Akbar (POLITICO, 2021)
This study aims to provide an overview of the supervision carried out by the Investment Agency and One Stop Services of Jember Regency on the licensing of karaoke business organizers in the city of Jember. In addition, this study also aims to provide an overview of the inhibiting factors in the implementation of supervision of the licensing of karaoke business operators in the City of Jember. The results showed that there were still many violations in the supervision of karaoke businesses in Jember City, such as violations of business licenses, and even many karaoke businesses that did not have a license and had not extended their business licenses. The results of this study also indicate the lack of awareness of karaoke owners about the applicable policies and in the process of making karaoke licenses. Relevant agencies responsible for supervising karaoke businesses are also less strict in making decisions or imposing sanctions on karaoke businesses that violate the rules. The main obstacle faced in supervising karaoke permits is the low awareness of the surrounding community to want to carry out supervision of the karaoke business and the lack of conditionality between related agencies in conducting supervision and providing information from one agency to another related to the karaoke business.